QLEDs: A General Solvent Selection Strategy for Solution Processed Quantum Dots Targeting High Performance Light‐Emitting Diode (Adv. Funct. Mater. 1/2017). (January 2017) - Zou, Yatao; Ban, Muyang; Cui, Wei; Huang, Qi; Wu, Chen; Liu, Jiawei; Wu, Haihua; Song, Tao; Sun, Baoquan
Abstract : On page 1603325, T. Song, B. Q. Sun, and co‐workers develop a general solvent selection strategy by taking interaction between quantum dots (QDs) and solvent into consideration. A suitable solvent is obtained to achieve a high quality QDs film for an efficient and uniformly emitting light‐emitting diode. This strategy provides a general approach to deposit high quality QDs films for solution‐processed multilayer optoelectronic devices.